Nutritional interventions for the treatment of frailty in older adults: A systematic review protocol - De Moraes, Mariana Bordinhon [UNESP]; Araujo, Carolina Fumico Massuda [UNESP]; Avgerinou, Christina; De Oliveira Vidal, Edison Iglesias [UNESP] (My University, 2018)
Background: Frailty has been defined as a clinical syndrome of multicausal origin characterized by a reduction of physiologic reserves that increase the vulnerability of an individual to adverse outcomes such as the development of functional dependence and death. Considered one of the most important geriatric syndromes, frailty's prevention and management represent important goals for gerontology and geriatrics. Although nutrition plays an important role within the multifactorial susceptibility for this syndrome, up to the present no systematic review specifically addressed the effectiveness of nutritional interventions for the treatment of frailty. Therefore, we propose the present systematic review with the aim to assess the effectiveness of nutritional interventions for the treatment of frailty in older adults living in the community or in long-term care facilities. Methods: We will search Medline (via Pubmed), Embase, Cinahl, Central, Lilacs, Web of Science, and sources of gray literature. We will accept trials whereby the unit of randomization consisted of individuals or clusters of individuals. Our primary outcome is all-cause mortality. Secondary outcomes are quality of life, functional status, cognitive function, frailty status, body composition, and physical activity. Risk of bias will be assessed using the Cochrane Collaboration tool. We will analyze the overall strength of the evidence for each outcome using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Two independent researchers will conduct all evaluations and any disagreements will be resolved through the participation of a 3rd author. If possible, we will perform random-effects meta-analyses and subgroup analyses concerning specific details of nutritional interventions (e.g., components and duration), research scenario, risk of bias, and criteria used to diagnose frailty. Conclusion: In this systematic review protocol we outline the details of the aims and methods of a systematic review on the effectiveness of nutritional interventions for the management of frailty in older adults living in the community or in long-term care facilities. We believe this wording to be more objective and balanced than the previous one. We understand that it is not ideal to propose changes to the text after manuscripts have been accepted. However, we feel that the new wording of the conclusion section of the abstract is more consistent with the overall content of the main text of the review than its previous version. Hence, we hope you may accept our request.
Keywords: Aged; Diet; Dietary supplements; Feeding; Frailty; Nutrition; Systematic review